ON THE NATURE OF MIGRATION MOVEMENTS IN THE REGIONS OF UZBEKISTAN (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The article analyzes the main trends observed in the migration movements of the population of the Republic of Uzbekistan and shows them on the example of the territorial migration movements of the population of Jizzakh region. It is worth noting that there is a commonality in the nature of population migration in all regions of the country. Therefore, the conclusions of the analysis carried out on the example of the territorial movements of the population of Jizzakh region can be applied to other regions of the country.